2018
DOI: 10.1111/sltb.12531
|View full text |Cite
|
Sign up to set email alerts
|

Texting for Help: Processes and Impact of Text Counseling with Children and Youth with Suicide Ideation

Abstract: Objective To explore: (1) how children contacting a child helpline with suicide ideation differ from children discussing other topics, (2) whether text messaging effectively helps, and (3) which counselor behaviors are most effective. Method Of 6,060 text sessions at the Danish national child helpline, 444 concerned suicidality, of which the 102 sessions that included self‐rated, end Session ratings were selected for content analysis. Results Twenty‐six percentage of suicidal children had severe suicidality. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…These findings support the emerging research on the psychosocial issues of users of text message-based hotlines who report suicidal ideation. Sindahl et al (22) reported that self-harm, bullying, and interpersonal problems were co-occurring issues for Danish texters who reported suicidal ideation. Mental health problems, issues with family or partners, and rumination were the most prominent co-occurring issues for users of the Dutch 113Online suicide prevention crisis chat service (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the emerging research on the psychosocial issues of users of text message-based hotlines who report suicidal ideation. Sindahl et al (22) reported that self-harm, bullying, and interpersonal problems were co-occurring issues for Danish texters who reported suicidal ideation. Mental health problems, issues with family or partners, and rumination were the most prominent co-occurring issues for users of the Dutch 113Online suicide prevention crisis chat service (27).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the interest in technology-enhanced crisis hotlines (8) and the use of text messages in suicide attempt prevention (20), more peer-reviewed studies on large-scale conversations of text message hotlines are needed (21)(22)(23). Because research suggests that individuals who report suicidality are often repeated users of text-based hotlines (22), in this study we aimed to increase knowledge by exploring distinct classes of texters who report suicidality by frequency of Crisis Text Line use and by whether the conversation was the first contact with the hotline, one of two contacts, or the last of several. Usage frequency highlights differences between individuals who have potentially acute versus ongoing issues, whereas conversation number among repeated texters allows insight into whether latent subgroups change by interaction with the hotline.…”
mentioning
confidence: 99%
“…Text-based crisis counseling services are a rather new and under-researched platform that offers youth in crisis access to cost-free and immediate help. Limited research has shown high acceptability among youth for these texting services and a subsequent reduction in suicide rates when used (Sindahl et al, 2018, Ranney et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest the utility of text-based counselling. For example, after a single text-messaging counselling session from a Danish children’s helpline, 35.9% of young people reported feeling better and more than half reported having a plan of action [ 24 ]. Similarly, Navarro, Bambling et al [ 18 ] reported young people perceived greater efficacy of text-based counselling with preferences for text-based communication (i.e., feeling heard/understood, catharsis, feeling normalised/validated/supported).…”
Section: Discussionmentioning
confidence: 99%
“…In response to increased use of, and some indication of preference for, text-based services, it is important that counsellors can provide appropriate support and guidance to meet young people’s needs in webchat contacts. Sindahl et al [ 24 ] suggest appropriate text-based support includes discussing emotions, expressing empathy, and encouraging the young person to speak to someone, while Navarro, Bambling et al [ 18 ] reported participants value feeling heard, understood, and supported during text-based contact. Moreover, given there is some indication that help-seeking by young people is low (e.g., [ 6 ]), appealing to preferred aspects of text-based counselling (e.g., safety, accessibility) [ 18 ], may increase the likelihood that young people engage with mental health services, including helplines.…”
Section: Discussionmentioning
confidence: 99%